Information avoidance, selective exposure, and fake(?) news: A green market experiment - Katharina Momsen; Markus Ohndorf (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2019)
We investigate if people exploit moral wiggle room in green markets when revelation is stochastic and the revealed information is potentially erroneous. In our laboratory experiment, subjects purchase products associated with co-benefits represented as a contribution to carbon offsets purchased by the experimenters. Information on the size of this contribution is unobservable at first, but can be actively revealed by the consumer. In seven treatments, we alter the information structure as well as the perceived revelation costs. We find strong evidence of self-serving information avoidance in treatments with simple stochastic revelation and reduced reliability of the information, representing potentially 'fake' news. The propensity to avoid information increases with the introduction of nominal information costs, which are in fact not payoff-relevant. We conclude that, generally, self-serving information avoidance can arise in green market situations if specific situational excuses are present, which could explain the demand for products associated with 'greenwashing'.
Keywords: C91; D12; D64; D89; Q50; 330; Information avoidance; experiment; carbon offsets; moral wiggle room; green consumption; fake news